Local Women's Perceptions Of Gender-Based Participation Role Sharing in Ngestirejo Village Development, Tanjungsari District, Gunungkidul Regency - Hasanati, Surani; Raden, Rijanta; Pitoyo, Agus Joko; Muliawati, Adina (UPT Publikasi Ilmiah UNISBA, 2026)
Abstract. Village development efforts require the involvement of parties in this matter, namely the community, both women and men in it. Local women's perceptions regarding the division of village development roles are needed to get perspectives from women actors themselves regarding the gender-based role division in Ngestirejo Village. Thus, this study aims to identify local women's perceptions of the division of male and female roles in the implementation of the Ngestirejo Village Development Planning Programme. This research is qualitative research using purposive sampling. Data collection method was carried out through observation, in-depth interviews with 17 informants, and secondary data review as a triangulation method. Data analysis was carried out by summarizing field findings into units of information and synthesizing these units of information into themes, which then culminated in inducing the themes into conceptual formulations related to the research topic. Thus, the result of the diversity of perceptions is seen in the emergence of themes, namely: understanding of gender-based role divisions; motivation for the division of roles; determination of core management; the composition of men and women in each team; women's responses to the division of roles; socio-cultural conditions; human capital; and will. There are two concepts derived from the induction of these themes, namely, gendered role sharing and participation. Thus, the expectations that can be identified related to gendered role sharing regarding implementation of the Ngestirejo Village Development Planning Programme are increasing teamwork cohesion and a more work-balanced composition.